ANALISIS IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN IPA DI MASA PANDEMI - Wida Khusnul Solikha; Martini Martini; Aris Rudi Purnomo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
The purpose of this study was to determine the application of a scientific approach to science learning during the pandemic at SMP Negeri 58 Surabaya. This type of research is descriptive qualitative. The data used is in the form of learning recordings carried out through web meetings such as Google Meet and Zoom.. The resource persons of this research are science subject teachers. Data collection techniques through observation, interviews, document studies and questionnaires. The analysis technique is through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the teacher had made a lesson plan with a scientific approach but the teacher had not explained it explicitly, systematically and comprehensively because the teacher found it difficult to determine the approach and model used during bold learning in each meeting. The implementation of learning by teachers has used a scientific approach, including the process of observing, asking questions, gathering information or trying, associating or reasoning and communicating but in its implementation it is still not optimally carried out there are several obstacles between passive students in learning, limited learning time and lack of ability of educators in learning. implement a scientific approach. Teachers use authentic assessments to assess the competence of attitudes, knowledge and skills of students. The teacher has not completed the assessment instrument and rubric because the teacher is not used to using the assessment instrument.